Peningkatan Motivasi Belajar Siswa Melalui Model Kooperatif Tipe STAD Pada Mata Pelajaran Pendidikan Agama Islam Kelas IV Sdn 01 Luhak Nan Duo - Buyung Kunar, S.Pd (STKIP Pesisir Selatan, 2016)
AbstractThe problems to be examined in this study is whether via the use of STAD learning methods to improve learning outcomes PAI fourth grade students of SDN 01 Luhak Nan Duo? The purpose of this action research to improve learning outcomes through the use of PAI learning method STAD type on the learner IV SDN 01 Luhak Nan Duo. This study usesclassroom action research as much as two rounds. Each round consists of four phases: planning, implementation, observation and reflection. Goal of this study is the fourth grade students of SDN 01 Luhak Nan Duo. The data obtained are quantitative and qualitative data. From the analysis of learning methods debriefing have a positive impact in improving the learning outcomes of students characterized by increased completeness of learners in each cycle, the first cycle (58.82%), the second cycle (88.24%). The conclusion of this study is the learning method STAD have a positive effect, which can increase learning outcomes of students shown by the average response of students stating that learners interested and are interested in the question and answer method of learning so that they become motivated to learn.Keywords: PAI, Type STAD Learning Methods